Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Call for Papers : The Impact of Black Lives Matter Movement in the Era of COVID-19 Pandemic - International Journal of Community Development & Management Studies (IJCDMS) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Redefining the Black Experience in Montreal: One Institution at a Time - The Project Woke Interns (Black Community Resource Centre (BCRC), 2020)
Project Woke interns identified and investigated three critical themes affecting the Black community in Montreal. An analysis of societal issues and Canada’s Anti-Racism Strategy Project revealed harmful anti-human rights gaps affecting the Black Community. The findings from several consultations further validated these gaps. A comprehensive list of recommendations is included along with next steps as a continuation to advance Black human rights in Montreal, and elsewhere, along with the support of government and non-government actors.

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)

Black Academic Scholarship Fund (BASF) and Education - Gaining Equity in Education and Empowering Black Learners - Piggott, Sylivia E. A. (Collaborative Unity and Existential Responsibility, 2019)
This article explains the movement for Africentric public schools in Canada, particularly in Montreal, and the controversy it has generated. It is also argued that Black youth would gain significantly from community based educational programs that root their learning more closely in the life, experiences and needs of their community.

Black and English-speaking in Montreal : an Intersectional Snapshot - Zehavi, Bonnie (Collaborative Unity and Existential Responsibility, 2019)
This paper presents a general overview of the challenges faced by English-speaking Black community members in Montreal, as well as the exacerbation of those barriers for individuals with a history of justice involvement. Frontline community initiatives focusing on education, employment, and entrepreneurship at DESTA Black Youth Network are profiled as an example of grassroots efforts to mitigate disparate circumstances between English-speaking Black Montrealers and their white counterparts. Statistical data in the areas of educational attainment, rates of unemployment, and income provide the platform for analysis and, recognizing the multiple identity experiences of belonging to a racialized and linguistic minority, an intersectional framework is employed. Recommendations for more race-based study, policy, and funding to better support equity strategies are provided.
Keywords: Official Language Minority Community (OLMC)

Empowering African-Canadian Career Excellence - Community Economic Development and Employability Corporation (CEDEC) (Collaborative Unity and Existential Responsibility, 2019)
The African-Canadian Career Excellence (ACCE) initiative was developed to address the loss of highly-educated, English-speaking Black youth from the Greater Montreal Area (Quebec, Canada) facing issues of unemployment and underemployment.
Keywords: Official Language Minority Community (OLMC)

Semaji - Black Community Resource Centre (BCRC) (2019)

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (Collaborative Unity and Existential Responsibility, 2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

Semaji - Black Community Resource Centre (BCRC) (2019)

Semaji - Black Community Resource Centre (BCRC) (2019)

Selected Papers from the 2018 Conference on Community Education and Development: Perspectives on English-Speaking Blacks and Minorities - Black Community Resource Centre (BCRC) (Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities, 2018)
The Black Community Resource Centre (BCRC) is a growing, resource-based organization that strengthens community capacity by providing professional support to organizations and individuals in need. The Centre is committed to helping visible minority youth rekindle their dreams, and achieve their full potential.We take a comprehensive approach to meet the needs of English-speaking youth. By referring to the “Holistic Project” approach through our community service, we recognize that youth have many needs (e.g., socio-cultural, educational, and economic, etc.) that must be addressed in order for youth to achieve their greatest potential in our society.
Keywords: Official Language Minority Community (OLMC)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

The Black Community Resource Guide 2010/2011 - Black Community Resource Centre (BCRC) (2011)

Semaji - Black Community Resource Centre (BCRC) (2010)

Semaji - Black Community Resource Centre (BCRC) (2010)

Semaji - Black Community Resource Centre (BCRC) (2010)

The Positive Ticket Pilot Program : A Feasibility Study - Low, Katherine (Black Community Resource Centre (BCRC), 2009)
The Positive Ticket Project was started in Richmond BC, and aims to improve the relationship between youth and police by way of positive interaction. Officers give out the positive tickets to neighbourhood youth displaying positive behaviour, which can be as simple as engaging in safe play or helping a community member. The positive tickets, which are business card size with positive messages printed on them, are combined with gift vouchers donated by and redeemable at local businesses. The real value of the project lies in the positive communication and interaction it creates between the officer and the youth. The Black Community Resource Center in Côte-des-Neiges wishes to implement a Positive Ticket Pilot Project in their neighbourhood in the summer of 2010.

Semaji - Black Community Resource Centre (BCRC) (2009)

Black Communities Speak Out About Violence - Tichit, Laurence; Jaccoud, Mylène (Black Community Resource Centre (BCRC), 2009)
This project was an initiative of six Black community organizations in Montreal concerned with the problem of violence. It was designed to unfold in three consecutive phases: 1) establish a subject overview by conducting focus groups with members of Montreal's Black communities, 2) organize a roundtable discussion with key people involved in the issue, and 3) develop an intervention plan. This report examines each of these phases which were aimed at defining the bases for mobilization and presenting possible strategies to address the issue of violence within the Black communities.

Semaji - Black Community Resource Centre (BCRC) (2008)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2008)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2008)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2004)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2004)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2004)

B.C.R.C. Newsletter - Black Community Resource Centre (BCRC) (2004)